Graves’ disease presenting as right heart failure with severe pulmonary hypertension - Khan, Furqan Mohd Akram; Mukherji, Anannya; Nabar, Shekhar T.; G, Ashwini (International Journal of Research in Medical Sciences, 2017)
We report a patient who presented to our institution with clinical features of right sided heart failure and hyperthyroidism. Diagnosis of grave’s disease induced reversible severe pulmonary hypertension leading to severe tricuspid regurgitation and right sided heart failure was made after all the common causes were ruled out using the biochemical and radiological investigations and review of literature. Graves’ disease is a common cause hyperthyroidism, is an immune system disorder that results in the overproduction of thyroid hormones.